DNA hydrogel delivery vehicle for light-triggered and synergistic cancer therapy1. Issue 21 (7th June 2015) - Song, Jaejung; Im, Kyuhyun; Hwang, Sekyu; Hur, Jaehyun; Nam, Jutaek; Ahn, G-One; Hwang, Sungwoo; Kim, Sungjee; Park, Nokyoung
<x xml:space="preserve">Abstract</x> A drug delivery vehicle has been prepared by combining gold nanorods and a DNA intercalated drug in a DNA hydrogel, resulting in thermo-chemo combination therapy with photothermal-triggered DNA melting and release of doxorubicin.